PENGEMBAGAN SISTEM PELAPORAN KEGIATAN KKN BERBASIS ANDROID - Danzen Hangga Permana; Aristoteles Aristoteles (Jurnal Komputasi, 2017)
This research was conducted to create a service learning activity reporting system which is able to assist BP-KKN, DPL and students in managing reports KKN.  The data of this research consists of the data DPL, the student, and the location of the KKN.  Data for KKN Unila Period I 2017 i.e. 55 DPL or lecturer from various faculties, 2708 students, and 387 location.  DPL data is used to test whether the system reports an activity that students upload was received directly by the DPL respectively.  Student data is used to test the system as students who are already registered as a participant of KKN that already get a token to login on this application.  While the village is used to find out the placement of the students and DPL as well as those of the village.  The results showed that: (1) functional testing using Black Box methods of Equivalence Partitioning (EP) getting results as expected on a test scenario in each test class.  (2) Ownership of smartphones and questionnaire testing provider with 135 people respondents consisting of students of KKN period I 2017 shows; ownership of Android-based smartphones to occupy the highest number i.e. 107 or 79.26%, while ownership provider Telkomsel occupies the highest number i.e. 100 or 74.07%. (3) the testing of the questionnaire android application with 40 respondents consisting of students of KKN period I 2017 shows; from the results of 5 statement on keusioner obtained an average value of 85.7% (categorized very good).  (4) the testing of the questionnaire web systems with 16 respondents consisting of DPL and KDPL KKN period I 2017 shows; from the results of the 4 statements on the questionnaire obtained average value of 81,875% (categorized very good).